Creating awareness and demand for gender work in agricultural research - Galiè, Alessandra (International Livestock Research Institute, 2016)
Interview with Alessandra Galie (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684